A non-invasive method for screening mitochondrial diabetes - Fang, Hangyu; Li, Xiaoe; Wang, Shuping; Zhang, Mei; Zhang, Victor Wei; Xu, Chao (Frontiers in Genetics, 2025)
BackgroundMitochondrial diabetes mellitus (MDM) is a special type of diabetes resulting from functional defects in mitochondria. Its incidence rate is low, and it can often be misdiagnosed as either type 1 or type 2 diabetes in clinical settings. Due to limited clinical experience in diagnosing and treating MDM, the rate of missed diagnosis is high. Therefore, employing appropriate detection methods for the rapid screening of suspected MDM patients can facilitate early diagnosis of MDM.MethodsWe conducted a multicenter observational study by collecting oral exfoliated cells from patients and detecting the m.3243A>G mutation using Polymerase Chain Reaction (PCR). We estimated the positivity rate of MDM and clinically evaluated the detection method through clinical trials. Additionally, we summarized the clinical phenotypes of patients who tested positive and compared the clinical manifestations between MDM and non-MDM patients using statistical analysis, providing a diagnostic foundation for clinicians.ResultsWe collected data from a total of 478 patients and identified 16 cases of m.3243A>G mutation-positive patients by collecting oral exfoliated cell samples for PCR testing, yielding a positivity rate of 3.35% and an asymptomatic carrier rate of 0.84%. These results are slightly higher than those reported in previous research. The gene mutation detection method demonstrated high credibility and was non-invasive, with a clinical sensitivity of 87.2% and clinical specificity of 96.9%. Additionally, patient satisfaction was high in this study. Statistical analysis revealed a significant difference in clinical manifestations between MDM and non-MDM patients. MDM patients were more likely to experience neurological hearing loss and multiple systemic manifestations, and their condition was consistent with maternal inheritance, in line with previous research findings.ConclusionThe detection of the m.3243A>G mutation through the collection of oral exfoliated cells offers several advantages over other methods, including simplicity, non-invasiveness, and high specificity and sensitivity. However, it is currently underutilized. Therefore, further experiments are needed to study and validate this approach in order to optimize MDM screening methods and improve diagnostic rates for MDM.